Telling the impact investment story through digital media: an Indonesian case study. Issue 4 (2nd October 2018) - Ryder, Paul; Vogeley, Joanna
ABSTRACT: In a marketplace still dominated by arcane legislative and regulatory architectures and by legacy communication processes, social enterprises are finding it difficult to secure funding. This qualitative research paper examined narratives of two entities: an Indonesian social enterprise and a Singaporean-based organisation that connects social enterprises with impact investors and adopts a multi-modal (across-method) research framework that includes both primary and secondary research. This paper develops a set of preliminary propositions regarding strategic communication via newly emergent digital conduits and the power of that tailored communication to positively impact the development of Southeast Asian social enterprises. The findings suggest that while much remains to be done before full digital integration is achieved, particular approaches (facilitating seamless and open digital communication between social enterprises and impact investors) are seeing social enterprises secure funding while contributing to the maturation of the social investment marketplace.